Theoretical foundations of the organization of tax control - Makhmatraemov Bakhrom Omonovich (Genius Journals, 2024)
In this article, research was conducted on ways to improve the methodological foundations of tax audits and evaluate their effectiveness, and conclusions and suggestions were formed within the framework of the research.
Keywords: tax; budget policy; budget; administration